A case report of reversible posterior encephalopathy syndrome with intracranial hemorrhage in a child. Issue 12 (26th March 2021) - Chen, Xiaoqian; Zhu, Weixue; Jiang, Suhua
Abstract: Introduction: The objective is to analyze the clinical diagnosis and treatment of children with rescindable posterior encephalopathy syndrome (PRES) and intracranial hemorrhage (ICH) to improve the pediatrician's understanding of PRES combined with ICH in children. Patient concerns and Diagnosis: After liver transplantation, the patient developed symptoms of epilepsy and coma. Meanwhile, massive necrosis of acute cerebral infarction and small hemorrhage was observed in the left cerebellar hemisphere and left occipital lobe, respectively. The above symptoms were initially diagnosed as PRES. Interventions and outcomes: After adjusting the anti-rejection drug regimen, it was found that the child's neurological symptoms were relieved, and the limb motor function gradually recovered during follow-up. Imaging examination showed significant improvement on abnormal signals in brain. Conclusion: In general, children with PRES may further develop ICH and contribute to a poor prognosis. Early diagnosis, detection of risk factors and timely adjustment of medication regimen are the keys to prevent irreversible brain damage.